EVALUATE RECOVERY OF PROSPECTIVE ELEMENTARY SCHOOL TEACHERS USING QUIZIZZ: IS IT EFFECTIVE? - Mohammad Archi Maulyda; Umar Umar (JURNAL EDUSCIENCE (JES), 2022)
The Covid-19 pandemic has a significant impact on Indonesia's education today. Students from both junior and senior batches of universities must experience changes in learning systems and models. Demands for change are felt not only by students but also by teachers. The teacher must meet the demands of distance learning. This also impacts on the use of appropriate tools in evaluating student learning outcomes. The Quizizz website is one of the teacher's tools for evaluating. However, it is not yet known whether Quizizz is the right tool for evaluating. The purpose of this study was to determine the effectiveness of using Quizizz as an evaluation tool. The research method is quantitative with quasi-experimental design. There are control and experiment classes, each with a sample of 37 students of Elementary School Teacher Education Study Program. Data obtained in the form of test score figures will be analyzed using independent t-test to find out whether the two data groups have significant mean differences. The "t-test for Equality of Means" column shows the results of the independent t-test. Sig. Value from the t-test is 0.138. If α = 0.05, then Sig.> 0.05. This shows that there is no significant difference between the experimental class and the control class. The results of the data analysis showed that there were no significant differences between the experimental and control classes. This shows that the use of the Quizizz website is less effective as a means of evaluating learning outcomes.The use of the quizizz website as a means of evaluating student learning outcomes needs to be further examined